2007
DOI: 10.1016/j.dmr.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Managing Bioterrorism Mass Casualties in an Emergency Department: Lessons Learned From a Rural Community Hospital Disaster Drill

Abstract: Bioterrorism represents a threat for which most emergency departments (EDs) are ill prepared. In order to develop an evidence-based plan for ED and hospital management of contaminated patients, a review was conducted of the most effective strategies developed during the severe acute respiratory syndrome (SARS) epidemic, as well as Centers for Disease Control and Prevention and military guidelines on biowarfare. Six basic steps were identified: 1) lock down the hospital and control access to the ED; 2) protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Luther et al (2006) carried out a study in an Australian ED using a mock simulation: areas of concern related to decontamination and the recognition of the situation at triage. Vinson's (2007) study carried out in a Pennsylvania ED, involving a simulated bioterrorist event had similar findings. Although the lessons learned following the simulation cannot be generalized to all hospitals, they highlight areas where responders continue to run into difficulties: primarily decontamination of patients and appropriate triage.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Luther et al (2006) carried out a study in an Australian ED using a mock simulation: areas of concern related to decontamination and the recognition of the situation at triage. Vinson's (2007) study carried out in a Pennsylvania ED, involving a simulated bioterrorist event had similar findings. Although the lessons learned following the simulation cannot be generalized to all hospitals, they highlight areas where responders continue to run into difficulties: primarily decontamination of patients and appropriate triage.…”
Section: Introductionsupporting
confidence: 78%
“…At the time of this study there was no UK research available that focused specifically upon nursing staff preparedness for a CBRNe incident: only that which assessed departmental capability by Anathallee et al, 2007. The UK is not alone in failing to adequately prepare for such major incidents. Luther et al (2006) and Vinson (2007) assessed staff preparedness within the ED for an incident relating to a chemical, biological and/or radiological threat, by simulating the event. No studies were found that also assessed the other two components of nuclear and explosive, grouped within the term CBRNe.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in this study highlighted the importance of staff training to combat HSI outbreak. Effective training would equip nurses with the knowledge and clinical skills applicable to patient care, which would benefit their capabilities for handling major health emergency threats such as pandemic situations (Leiba et al, 2006;Vinson, 2007). In addition to enhancing the pandemic preparedness of the frontline staff through preliminary training, the smooth functioning of the healthcare institution in response to disease outbreaks should also be maintained (Hynes, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The utility of exercises using simulated incident scenes for improving the response performance has been reported by a limited number of publications. [6][7][8][9][10][11][12] Methods of monitoring and evaluation of response activities include: (1) a post-exercise self-assessment questionnaires for rescue workers; 7,11 (2) post-exercise questionnaires filled out by simulated victims; 11 and (3) the use of trained, external observers. 11,13 However, the methods used for documentation and evaluation usually are kept confidential.…”
Section: Data Processingmentioning
confidence: 99%